2014
DOI: 10.1111/jcmm.12363
|View full text |Cite
|
Sign up to set email alerts
|

A novel functional interplay between Progesterone Receptor‐B and PTENvia AKT, modulates autophagy in breast cancer cells

Abstract: The tumour suppressor activity of the phosphatase and tensin homologue on chromosome 10 (PTEN) is subject of intense investigative efforts, although limited information on its regulation in breast cancer is available. Herein, we report that, in breast cancer cells, progesterone (OHPg), through its cognate receptor PR-B, positively modulates PTEN expression by inducing its mRNA and protein levels, and increasing PTEN-promoter activity. The OHPg-dependent up-regulation of PTEN gene activity requires binding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 48 publications
(55 reference statements)
2
29
0
Order By: Relevance
“…Progesterone receptors action in mediating progesterone effects is highly context dependent and heavily influenced by post-translational modifications [ 4 ] as well as cofactor availability [ 5 ]. Several independent in vitro studies have demonstrated the inhibitory action of progesterone on breast cancer cell growth [ 6 8 ] and in agreement with these findings in a very recent paper we report that hydroxyprogesterone (OHPg), via PR-B isoform, leads to a reduced cell survival due to autophagy induction [ 9 ] through PTEN up-regulation.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Progesterone receptors action in mediating progesterone effects is highly context dependent and heavily influenced by post-translational modifications [ 4 ] as well as cofactor availability [ 5 ]. Several independent in vitro studies have demonstrated the inhibitory action of progesterone on breast cancer cell growth [ 6 8 ] and in agreement with these findings in a very recent paper we report that hydroxyprogesterone (OHPg), via PR-B isoform, leads to a reduced cell survival due to autophagy induction [ 9 ] through PTEN up-regulation.…”
Section: Introductionsupporting
confidence: 89%
“…Beclin-1 is a component of the class IIIPI3 kinase complex which is required for autophagy activation by various stimuli [ 23 , 24 ]. Stemming from our data indicating that 10 nM OHPg via PR-B [ 9 ] increases protein and mRNA levels of Beclin-1 in T47-D and MCF-7 cells (Figure 1A-1C ), we next investigated the effects of OHPg/PR-B on Beclin-1 gene transcription. To this aim we performed transient transfection studies by using the 5′ flanking region of Beclin-1 expression vector and two different deleted constructs (Figure 2A , left panel ) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/Akt/mTOR signaling pathway has been reported to be an important negative regulator of autophagy ( Heras-Sandoval et al, 2014 ). PTEN can regulate autophagy in mammalian cells by antagonizing PI3K through its lipid phosphatase activity ( De Amicis et al, 2014 ). Moreover, PTEN can also affect the brain development as suggested by its abundant expression in embryonic central nervous system ( Gimm et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the TransAttack study showed that the lowest PgR percentage quartile had an unfavourable prognosis as compared to the highest quartile [ 50 ]. A proposed mechanism is that ligand activation of PgR induces PTEN expression and thereby inhibits the PI3K/AKT pathway [ 51 ]. In addition, PgR associates with ERα resulting in an increased anti-proliferative effect by a unique gene expression program that is associated with good clinical outcome.…”
Section: Discussionmentioning
confidence: 99%